ANALISIS TOTAL PRODUCTIVE MAINTENANCE (TPM) PADA MESIN FILLING VIAL DI PT. MERSIFARMA TM - HEPPI FAMILIANA (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2024)
The smooth production process requires support from good machinery and equipment conditions. The availability of good machinery and equipment will greatly assist the company in achieving all production targets with good quality standards. Various obstacles are often encountered when production is in progress. If this condition continues to occur, it will hamper the production process and make it difficult to achieve the targets set by the company. Therefore, a proper maintenance program is needed in handling it. To be able to calculate and increase the level of effectiveness in the end, it is necessary to approach all aspects. One approach that can be used is the measurement of Overall Equipment Effectiveness (OEE) as a product of Total Produdctive Maintenance (TPM). The values resulting from the OEE calculation will refer to the various constraints experienced by the machine. Based on observations and data processing that has been carried out, the average value of OEE in January 2024 is 46.87% with an Availability value of 98.81%, Performance 49.26% and Quality Rate 96.30%. The average OEE value in February 2024 is 46.60% with an Availability value of 98.65%, Performance 49% and Quality Rate 96.42% and the OEE value in March 2024 is 47% with an Availability value of 98.75%, Performance 49.18% and Quality Rate 96.41%.